Institutionalist Perspectives on Development A Multidisciplinary Approach (Palgrave Studies in Democracy, Innovation, and Entrepreneurship for Growth,, 2018)
This book depicts the role of both formal and informal institutions in achieving long-term economic efficiency and development. It is organized into three sections: the first section deals with the historical and political roots that make institutions favorable to development; the second section offers theoretical perceptions of immaterial institutions; the last section explores how the various official institutions - such as international organizations - interrelate with the process of development. As both the recent global financial crisis and the subsequent sovereign debt crisis within the Eurozone have shown, sustainable development is a combination of human, social and institutional factors that interact with each other and go beyond the strictly economic conditions of each country. With contributions from several countries in Europe as well as Iran, this volume offers readers an international and multidisciplinary perspective of the institutionalist determinants of growth in the long run.